Post-2020 climate action : global and Asian perspectives - Fujimori, Shinichiro; Kainuma, Mikiko; Masui, Toshihiko (Springer, 2017)
This book summarizes assessments of the Paris Agreement to provide an excellent introduction to this research field. The AIM/CGE (Asia-Pacific Integrated Modeling /Computable General Equilibrium) model, which is the core of AIM modeling framework, is used for the assessment. The first part focuses on global issues, presenting both short-term (a few decades) and long-term (century scale) assessments in the context of the Agreement's ultimate climate goal. It also discusses policy implementation and climate risk. Part 2 is a collection of assessments of individual Asian countries, providing insights into the national situations and detailed analyses. It includes contributions from Asian countries as well as NIES (National Institute for Environmental Studies, Japan) members. The main conclusion is that many countries require changes to their energy systems change and societal transformation in order to meet emissions targets. Part 3 describes in detail the AIM/CGE model, which is used to evaluate the climate and energy policies by simulating the future economic and energy and environmental situation in the Asia-Pacific region. This section can be used as a standard text on CGE modelling in climate change mitigation.